Efficacy of Methotrexate Treatment, Nonsurgical Treatment of Ectopic Pregnancy (EP) - Humaira Bibi, Shamim Akhter, Saba Nasir, Bushra Sadia (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Methotrexate treatment of ectopic pregnancies is not only effective but also safe and saves fallopian tube without major side effects related to surgery. Aim: To determine the efficacy of Methotrexate for treatment of women with EP. Study design and period: retrospective observational study 1 years from July 2021 till July 2022. Setting: Department of Obstetrics & Gynaecology, Abha Maternity and Children hospital, Aseer Region Saudi Arabia. Methods: This was a retrospective observational study, in which 52 women with EP were included and were given injection methotrexate 50 mg/m2 intramuscularly. The β-hCG level was measured before treatment and then on 7th day of treatment. If β-hCG was reduced by >15% of pre-treatment levels on day 7 then it was called as successful treatment. Results: The overall success rate of this regimen was 73% of patients, including 6% of those who required second dose. 27% of patients underwent surgery and were designated as treatment failures. The mean β-hCG level before treatment was significantly lower in the treatment success group than in the treatment failure group (1491.79 ± 1094.69 vs 2701.50 ± 1417.28 IU/L, p= 0.0381). Sac size was considered statistically increased in the treatment failure group, ie, 3.75 ± 0.29 (P < 0.05). Conclusion: Based on the findings of our study, it can be stated that methotrexate treatment is very effective in the treatment of patients with ectopic pregnancy and can be recommended as a first-line treatment in patients with a low initial β-hCG level and a small ectopic pregnancy sac size. Keywords: ectopic pregnancy; methotrexate; operative laparoscopy; β-hCG; sac size